Adhesin proteins in Bacillus cereus biofilms - Caro-Astorga, Joaquín; Pérez-García, Alejandro; De-Vicente-Moreno, Antonio; Romero-Hinojosa, Diego Francisco (My University, 2015)
The human pathogen Bacillus cereus is responsible for many recurrent outbreaks of food poisoning. Spores and biofilms are considered the most important reservoirs of B. cereus in contaminated fresh vegetables and fruits. Bacterial biofilms are difficult to eradicate specially due to the presence of a protective extracellular matrix made of exopolysaccharides, proteins, and other components. Amyloid-like proteins are essential for the integrity of biofilms of the related bacteria species Bacillus subtilis. Objectives: To investigate the presence of amyloid-like fibers in biofilms of B. cereus. Methods: We identified two genomic loci in B. cereus, which encode two orthologues of the amyloid-like protein TasA and a SipW signal peptidase of B. subtilis. Mutagenesis in B. cereus or heterologous expression of alleles in B. subtilis mutants combined with crystal violet staining served to evaluate the formation of biofilm. Electron microscopy let us visualize the presence of fibers on cells. Conclusions: We demonstrate that the proteins TasA and CalY are necessary for B. cereus biofilm formation: i) as pellicle on the air-liquid interphase or ii) adhesion to abiotic surfaces. TasA and to a lesser extent CalY polymerizes in the form of fibers in the cell surface. Our findings of heterologous expression in B. subtilis let us propose an amyloid-like nature of the B. cereus TasA-based fibers
Keywords: Bacillus cereus